Small, young, and exporters: New evidence on the determinants of firm growth - Marco Grazzi; Daniele Moschella (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2016)
This work investigates how the export status of the firm influences the patterns of growth at different age classes. We address this research question resorting to a novel set of data that links together the universe of Italian firms and detailed data on export transactions. We find that the positive relationship between export status and growth declines with firm age. Further, we also find that, even when accounting for the role of age, the negative size-growth relationship does not disappear, contrary to some recent evidence. These results, which are robust to a series of controls, suggest for a positive signaling role of the export status which is stronger for young exporters or born globals. Exploiting the product-country level dimension of the customs data we also provide, for the first time, evidence on differences in exchange rates pass through between young and experienced exporters. In particular, we find that early exporters appear to be well equipped to face exchange rates variations as their exports decrease less following a currency appreciation.
Keywords: D22; F14; L11; L21; L25; 330; Firm age and performance; Firm growth; International trade; Born global; Exchange rates pass-through